PENGARUH TINGKAT PENDIDIKAN DAN TINGKAT PENDAPATAN TERHADAP MINAT BERWAKAF UANG DENGAN RELIGIUSITAS SEBAGAI VARIABEL MEDIASI PADA ASN MUSLIM KOTA PALEMBANG - Rahma Juliana; Muthmainah Juniawati; Safitri Asrol (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to determine the effect of education level and income level on interest in cash waqf with religiosity as a mediating variable. This is a quantitative study. The population consists of 90 Muslim civil servants. Data were collected using a Likert scale questionnaire, validity and reliability testing, and hypothesis testing using SmartPLS 4.0 software. The results of the study indicate that educational level has a positive and significant effect on religiosity, income level has a positive and significant effect on religiosity, educational level does not affect interest in monetary waqf, income level has a positive and significant effect on interest in monetary waqf, & religiosity has a positive & significant effect on interest in monetary waqf. Educational level has a positive and significant effect on interest in monetary waqf with religiosity as a mediating variable, and income level has a positive and significant effect on interest in monetary waqf with religiosity as a mediating variable. Therefore, it is recommended that the government implement regular religious programs in the work environment of Muslim civil servants because religiosity has been proven to be the main factor driving interest in monetary waqf.